The Impact of Opportunity Zones on Private Investment and Economic Activity - Kevin Corinth; Naomi Feldman (American Enterprise Institute (AEI), 2023)
Place-based policies aim to stimulate economic development in disadvantaged areas with the goal of improving the well-being of residents. A provision of the Tax Cuts and Jobs Act aimed to spur private investment in low-income areas called Opportunity Zones (OZs). We evaluate the impact of OZs on investment using data on the near-universe of commercial retail, office, and industrial real estate investments in the United States and a regression discontinuity design that exploits randomness near the OZ eligibility threshold. From 2019-2022, we find economically small and statistically insignificant point estimates of the effect of OZ eligibility on census tract-level investment. Additional data from MasterCard show no robust evidence of increased business activity nor consumer spending. However, we find suggestive effects on investment in multi-family housing in certain years. We conclude that almost five years after the OZ policy was implemented, there is no evidence of a private investment response that has spread beyond multi-family housing, limiting the potential of the policy to stimulate broad economic development and improve the well-being of residents.
Keywords: H53; E22; D61; 330; Opportunity zones; investment; tax policy; poverty